2017
DOI: 10.1371/journal.pgen.1006706
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of 79 loci for 83 plasma protein biomarkers in cardiovascular disease

Abstract: Recent advances in highly multiplexed immunoassays have allowed systematic large-scale measurement of hundreds of plasma proteins in large cohort studies. In combination with genotyping, such studies offer the prospect to 1) identify mechanisms involved with regulation of protein expression in plasma, and 2) determine whether the plasma proteins are likely to be causally implicated in disease. We report here the results of genome-wide association (GWA) studies of 83 proteins considered relevant to cardiovascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
223
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 252 publications
(261 citation statements)
references
References 39 publications
4
223
1
Order By: Relevance
“…Folkersen et al [48] recently reported similar association between SNPs in the same gene loci on chromosome 20 and plasma SCF with the strongest association found for rs4810479. We identified four SNPs in genes on chromosome 20 that demonstrated genomewide significant association with the plasma level of SCF.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Folkersen et al [48] recently reported similar association between SNPs in the same gene loci on chromosome 20 and plasma SCF with the strongest association found for rs4810479. We identified four SNPs in genes on chromosome 20 that demonstrated genomewide significant association with the plasma level of SCF.…”
Section: Discussionmentioning
confidence: 75%
“…Three of these were in linkage disequilibrium and regression analysis indicated that the strongest association was with a SNP in the PCIF1 gene. Folkersen et al [48] recently reported similar association between SNPs in the same gene loci on chromosome 20 and plasma SCF with the strongest association found for rs4810479. All four SNPs identified to have genomewide significance with plasma SCF in the present study were significantly associated with plasma SCF also in the study by Folkersson et al with both rs7679 and rs6065904 reaching genomewide significance.…”
Section: Discussionmentioning
confidence: 75%
“…Genome-wide association (GWA) analyses could identify these genes or variants. There are several GWA studies of FA (Elliott et al, 2017;Lopez et al, 2012;Sprooten et al, 2013Sprooten et al, , 2014 and inflammatory measures (Ahola-Olli et al, 2017;Emilsson et al, 2018;Folkersen et al, 2017;Kim et al, 2012;Larsen et al, 2013;Li et al, 2016;Sun et al, 2018). While these analyses successfully identify loci underlying individual variation in these traits, they fail to identify variants common to both.…”
Section: Discussionmentioning
confidence: 99%
“…One attractive solution is described for coupling multiplexed protein detection with read-out by DNA and to profile more than 90 proteins in a single assay (70, 71); they have been used and applied in extensive sample sets (72, 73). While these proximity extension assays use two binders per target protein, other large scale techniques employ single affinity reagents for high multiplexing capabilities.…”
Section: Assay Platformsmentioning
confidence: 99%